(untitled) (R&D Journal, 2018)
This study is a fundamental investigation to demonstrate the effect of significant deceleration on the transonic flow field around a blunt cylindrical projectile through a numerical approach implemented in ANSYS Fluent. The projectile geometry and order of acceleration magnitude is based on a study by Jiang et al. [1], who investigated the near blast flow-field of a supersonic projectile emerging from a barrel into ambient air using an Euler solver. This study considers the region of flight once the projectile has travelled away from the barrel outlet. Two projectile shapes is considered (25×25 mm and 50×25 mm cylinders) and two deceleration magnitudes (10 000 m/s2 and 5 000 m/s2). The projectiles are decelerated from steady state Mach 1.2 to 0.8, at zero-incidence. The bow shock and wake recovery compression waves are shown to propagate forward relative to the body where the wake recovery compression waves overtake the body and appear ahead of the nose. Strong coupling exists between the near wake flow field and outer region of the separation bubble on the cylinder for an aspect ratio of 1, influencing the shock dynamics during deceleration.